Concepts of occlusion in prosthodontics: A literature review, part II - V Rangarajan; P B Yogesh; B Gajapathi; M Mohamed Ibrahim; R Ganesh Kumar; Murali Karthik (Wolters Kluwer Medknow Publications, 2016)
This series of articles describes about concepts of occlusion in the complete denture, fixed partial denture, and implants. This article discusses about the evolution of different concepts of nonbalanced occlusion and occlusal schemes in complete denture occlusion.